Estrategias lúdicas para el aprendizaje significativo en la asignatura de estudios sociales en estudiantes de octavo año de la escuela de educación básica Antonio Parra Velasco - Suárez Armijo, Cindy Lisbeth (2024)
The objective of this research is to analyze recreational strategies and their relationship with meaningful learning in the subject of Social Studies in eighth-year basic education students at the Antonio Parra Velasco School. For this process, research with a quantitative and qualitative approach was applied, using the analytical-synthetic method. Likewise, a bibliographic research was carried out, as it was relevant to know the historical academic background of the institution, programs, operational plans, theories, concepts and approaches. For its part, the selected techniques were observation, interviewing the manager and surveying teachers and students, using a questionnaire. In relation to the population, it was made up of a sample of 21 students and 11 teachers from the eighth year of basic education at the Antonio Parra Velasco School of the Mocache Canton. Based on the results, 95% of the students consider that the application of playful strategies allows the improvement of significant learning and understanding of the subject of Social Studies, on the other hand; 95% thought that the playful strategy can be a good option for those students who have difficulties learning this subject. For its part, it is considered appropriate to innovate teaching actions through the development of a teacher training plan aimed at the application of recreational strategies with the help of technology to improve the meaningful learning of students.